2021
DOI: 10.1007/s00268-021-06309-8
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Chemotherapy in the Treatment of Intraductal Papillary Mucinous Neoplasms of the Pancreas: Systematic Review and Meta‐Analysis

Abstract: Background The present systematic review aimed to compare survival outcomes of invasive intraductal papillary mucinous neoplasms (IIPMNs) treated with adjuvant chemotherapy versus surgery alone and to identify pathologic features that may predict survival benefit from adjuvant chemotherapy. Method A systematic search of MEDLINE, PubMed, Scopus, and EMBASE was performed using the PRISMA framework. Studies comparing adjuvant chemotherapy and surgery alone fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Recent studies including a meta-analysis suggested no major survival benefit with adjuvant chemotherapy; however, all the included studies are retrospective in nature. 23,25 Such a fundamental decision in patient management, however, will require a prospective randomized controlled trial of surgery alone versus surgery with adjuvant chemotherapy and to be adequately powered to answer this question. [26][27][28][29] Significant advances in molecular subtyping of PDAC have identified distinct subtypes of PDAC with particular characteristics in tumor biology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies including a meta-analysis suggested no major survival benefit with adjuvant chemotherapy; however, all the included studies are retrospective in nature. 23,25 Such a fundamental decision in patient management, however, will require a prospective randomized controlled trial of surgery alone versus surgery with adjuvant chemotherapy and to be adequately powered to answer this question. [26][27][28][29] Significant advances in molecular subtyping of PDAC have identified distinct subtypes of PDAC with particular characteristics in tumor biology.…”
Section: Discussionmentioning
confidence: 99%
“…The recent European guidelines, however, recommend adjuvant chemotherapy for adenocarcinoma arising IPMN with or without nodal disease. Recent studies including a meta-analysis suggested no major survival benefit with adjuvant chemotherapy; however, all the included studies are retrospective in nature 23,25 . Such a fundamental decision in patient management, however, will require a prospective randomized controlled trial of surgery alone versus surgery with adjuvant chemotherapy and to be adequately powered to answer this question 26–29 .…”
Section: Discussionmentioning
confidence: 99%
“…In another retrospective study on 103 patients collected from 1993 to 2018, Rodrigues et al examined the impact of adjuvant chemotherapy and found that it could not provide survival benefits in node-negative patients but even compromise the prognosis (24). However, a systematic review of 11 studies and 3,393 invasive IPMNs found that node-positive patients could benefit from adjuvant chemotherapy (25). In order to determine the potential role of chemotherapy in the invasive IPMN cohort, we assessed the outcomes between patients who underwent surgery alone and those who received surgery plus chemotherapy after adjusting for confounding by the PSM method.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis aimed to compare survival outcomes of invasive intraductal papillary mucinous neoplasms (IPMNs) treated with adjuvant chemotherapy versus surgery alone [11 ▪ ]. Eleven studies and 3393 patients were included.…”
Section: Adjuvant Therapy New Data and Effectiveness In Specific Subg...mentioning
confidence: 99%